Teachers’ Perception Toward English Curriculum in KTSP and 2013 Curriculum at Sma Negeri 1 Bontonompo Selatan Gowa, SMA Negeri 2 Sungguminasa - Nehru P. Pongsapan (Teaching English as a Foreign Language Overseas Journal, 2017)
Curriculum in KTSP and 2013 Curriculum at SMA Negeri 1 Bontonompo SelatanGowa, SMA Negeri 2 Sungguminasa Gowa and SMK Negeri 1 Patalassang Gowa.The researcher used descriptive method. The researcher gives the instrument testthen the data gained was analyzed by using percentage. The population of thisresearch was the entire English teacher of SMA Negeri 1 Bontonompo SelatanGowa, SMA Negeri 2 Sungguminasa Gowa and SMK 1 Patalassang Gowa, Totalnumber of population was 9 Teachersthe result of this research,1. Most of the teachers found that, 2013 Curriculum is easier to implemented andnot too troublesome for teachers because many facilities available comparedto the KTSP and the ultimate goal of the 2013 Curriculum was also very good,accordance with the demands of time.2. There are some constraints in implementing the 2013 Curriculum namely: thelack of text book from the government, the absence of cross-interest training,and unequal school facilities and infrastructure .3. The difficulties in teaching English based KTSP and 2013 Curriculum namely:in KTSP there is no provision guidebook for teachers and teks book forstudents and the teachers must create their own learning device. It is veryburdensome for teachers and make them less focus.